2019
DOI: 10.1097/md.0000000000015608
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor variant 7 (AR-V7) in sequencing therapeutic agents for castratrion resistant prostate cancer

Abstract: Background: androgen receptor variant 7 (AR-V7) has been suggested as potential marker for treatment selection in men with metastatic castration-resistant prostate cancer (mCRPC). The aim of the present review is to critically analyze: frequency of the AR-V7 expression in mCRPC cases—impact of AR-V7 expression on abiraterone, enzalutamide, and taxane therapy. Methods: we searched in the Medline and Cochrane Library database from the literature of the past 10 years. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…In the Sciarra review, the mCRPC AR-V7 positive rate was reported at 18.3% (range 17.8-28.8%) [21], and our Celsee AR-V7 positive rate was similar at 22.0%. However, whether the detected AR-V7 is really derived from CTCs cannot be confirmed by the detection rate.…”
Section: Discussionsupporting
confidence: 60%
“…In the Sciarra review, the mCRPC AR-V7 positive rate was reported at 18.3% (range 17.8-28.8%) [21], and our Celsee AR-V7 positive rate was similar at 22.0%. However, whether the detected AR-V7 is really derived from CTCs cannot be confirmed by the detection rate.…”
Section: Discussionsupporting
confidence: 60%
“…The purpose of medical treatment for mCRPC is to slow down the disease progression. In this regard, traditional therapeutic approaches have consisted of hormonal therapy, chemotherapy, bisphosphonates, and best supportive care [17][18][19] . The large number of studies accomplished to evaluate the oncological outcomes among PCa patients treated with RP or EBRT have brought conflicting results [20][21][22] .…”
Section: Management Of Mcrpcmentioning
confidence: 99%
“…Taxane therapy is more efficacious than ARAT agents in AR-V7-positive patients. However, the clinical outcomes did not seem to differ significantly on the basis of the type of therapy used in AR-V7-negative patients [43]. In addition, several studies suggested that docetaxel chemotherapy may produce resistance to AR [14,15].…”
Section: Discussionmentioning
confidence: 93%